Congenital Pouch Colon: Case Series and Review of Evidences for Resection - Duci, Miriam (J Indian Assoc Pediatr Surg, 2021)
BACKGROUND: Congenital pouch colon (CPC) is a rare variant of anorectal malformations (ARM) with its highest reported incidence in India. We aimed to describe five patients affected by CPC, in which the tissue from the terminal dilated colon has been successfully used and to discuss our results on the light of an extended revision of the literature. MATERIALS AND METHODS: The clinical details of five cases treated for CPC in two Italian Centers were retrospectively reviewed assessing the fate of the terminal dilated colon. RESULTS: In all cases, the tissue from dilated colon has been used. The double vascular system of the dilated pouch allowed increasing bladder capacity (case 4), reconstruction of the vagina (case 3, 5), and lengthening of the colon (case 1, 2, 5).In our series, 3/5 have a good bowel control with daily bowel management after ARM correction. In literature, there are not differences in terms of dependence from bowel management in patients with pouch resected and in patients with pouch saved (P = 0.16). CONCLUSIONS: We acknowledge that the analysis of the available literature is limited by the absence of studies with high level of evidence and the removal or the preservation of the abnormal colon tissue seems to follow the surgeon preferences.